MEKTEPKE SHEKEMGI JASTAǴÍ BALALARDA DÚNYAǴA KÓZ QARASTÍ QÁLIPLESTIRIWDE ESTETIKALÍQ QÍYALLARDÍŃ ORNÍ - Jumasheva, G. (SCIENCE and SOCIETY, 2023)
The article considers the formation of aesthetic concepts in preschool children as a social and pedagogical problem. Reveals the essence of the concept of family, aesthetic education and spiritual development of the individual in the family. The article is devoted to the study of the problem of raising spirituality and morality in the family, increasing the effectiveness of aesthetic education in children in the family, which provided an opportunity to join the culture of their people and universal human values.